2007
DOI: 10.1007/s10709-007-9217-7
|View full text |Cite
|
Sign up to set email alerts
|

Shape and size variation on the wing of Drosophila mediopunctata: influence of chromosome inversions and genotype-environment interaction

Abstract: The second chromosome of Drosophila mediopunctata is highly polymorphic for inversions. Previous work reported a significant interaction between these inversions and collecting date on wing size, suggesting the presence of genotype-environment interaction. We performed experiments in the laboratory to test for the joint effects of temperature and chromosome inversions on size and shape of the wing in D. mediopunctata. Size was measured as the centroid size, and shape was analyzed using the generalized least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
(40 reference statements)
0
12
0
1
Order By: Relevance
“…This pattern suggests that natural selection is maintaining the observed variation (Ananina et al 2004, Klaczko 2006. Hatadani & Klaczko (2008) showed that Drosophila mediopunctata wing size and shape were influenced by second chromosome karyotype, sex, and temperature under controlled laboratory conditions. They also found evidence of interaction between karyotype and temperature on wing shape, suggesting the existence of genotype-environment interaction on this character, and that this interaction may be correlated with temperature differences across seasons.…”
Section: Introductionmentioning
confidence: 88%
“…This pattern suggests that natural selection is maintaining the observed variation (Ananina et al 2004, Klaczko 2006. Hatadani & Klaczko (2008) showed that Drosophila mediopunctata wing size and shape were influenced by second chromosome karyotype, sex, and temperature under controlled laboratory conditions. They also found evidence of interaction between karyotype and temperature on wing shape, suggesting the existence of genotype-environment interaction on this character, and that this interaction may be correlated with temperature differences across seasons.…”
Section: Introductionmentioning
confidence: 88%
“…Bitner-Mathé et al (1995) found a genotype (karyotype for inversions) 9 environment (collecting date) for wing size, as well as a clear effect of karyotype on wing shape. In the laboratory, Hatadani and Klaczko (2008) showed a clear influence of karyotype on size and shape of the wing. Finally, from a geographical standpoint, we found that populations that lie on the Serra da Matiqueira show high frequencies (*50%) of DA-PA0 while this haplotype is rare in Southern Brazilian populations (unpublished data and Ananina et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to avoid biases on the genetic structure estimates by hitchhiking effect due to selection on chromosome inversions (Kennington & Hoffmann, 2013;Santos et al, 2016), one may use microsatellite loci located in the inversion-free chromosomes (Cavasini, Batista, & Klaczko, 2015;Laborda, Gazaffi, Garcia, & Souza, 2012). On the other hand, adaptive responses can be inferred from chromosome II inversion polymorphism, which is associated with variation in other traits that affect fitness, such as size and shape of the wing and genitalia and polychromatism (Andrade, Vieira, Ananina, & Klaczko, 2009;Bitner-Mathé, Peixoto, & Klaczko, 1995;Hatadani & Klaczko, 2008;Hatadani, Baptista, Souza, & Klaczko, 2004). Furthermore, chromosome II inversion polymorphism shows correlation with climatic variables (temperature and precipitation) congruent with an altitudinal cline and seasonal cycling variation described for the natural population from Parque Nacional do Itatiaia, Rio de Janeiro State (Ananina et al, 2004;Batista et al, 2012;Klaczko, 2006).…”
Section: Drosophila Mediopunctatamentioning
confidence: 99%